Android Based E-Questionnaire for WIFI Services - Solehatin Solehatin; Chairul Anam (Universitas Ahmad Dahlan, 2019)
In the Banyuwangi regency area there is a wifi service that is specifically for students, government agencies, and urban and rural communities. Hopefully everything can be done quickly and easily by utilizing internet services. To find out the level of utilization of existing services, research is conducted by making an information system. In this study an application system made based on Android using a questionnaire. The application is made based on android in the form of an E-Questionnaire that can help to access and find out the level of utilization of wifi service